Association between dd‐cfDNA levels, de novo donor specific antibodies, and eGFR decline: An analysis of the DART cohort. Issue 9 (14th July 2021) - Sawinski, Deirdre L.; Mehta, Shikha; Alhamad, Tarek; Bromberg, Jonathan S.; Fischbach, Bernard; Aeschbacher, Thomas; Ghosh, Srinka; Shekhtman, Grigoriy; Dholakia, Sham; Brennan, Daniel C.; Poggio, Emilio; Bloom, Roy D.; et al.
Abstract: Background: Donor‐derived cell‐free DNA (dd‐cfDNA) is a marker of allograft injury in transplant recipients; however, the relationship between dd‐cfDNA and other clinical parameters associated with adverse allograft outcomes is not well‐characterized. Methods: We performed a retrospective analysis of kidney transplant recipients from the DART cohort (ClinicalTrials.gov Identifier: NCT02424227) to evaluate the associations between eGFR decline, de novo donor‐specific antibodies (dnDSA), and dd‐cfDNA. Results: Both elevated dd‐cfDNA (≥1%) and dd‐cfDNA variability (≥.34%) in the first post‐transplant year were associated with decline in eGFR ≥25% in the second year (21.4% vs. 4.1%, P  = .005; 25% vs. 3.6%, P  = .002, respectively). Compared to samples from DSA negative patients, samples from patients with concurrent de novo HLA DSAs had higher dd‐cfDNA levels ( P  < .0001). Discussion: Abnormalities in dd‐cfDNA levels are associated with clinical parameters commonly used as surrogate endpoints for adverse allograft outcomes, raising the possibility that molecular injury as characterized by dd‐cfDNA could help identify patients at risk of these outcomes.